(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The research reported in this paper explores the nature of student knowledge about group theory, arid how an individual may develop an understanding of certain topics in this domain. As part of a long-term research and development project in learning and teaching undergraduate mathematics, this report is one of a series of papers oil the abstract algebra component of that project.We end the paper with a brief discussion of some pedagogical suggestions arising out of our considerations. We defer, however, a full consideration of instructional strategies and their effects oil learning these topics to some future time when more extensive research can provide a more solid foundation for the design of specific pedagogies.